Diversity and antimicrobial activity of mangrove soil actinomycetes isolated from Tanjung Lumpur, Kuantan - Abdul Malek, Nurfathiah; Zainuddin, Zarina; Khan Chowdhury, Ahmed Jalal; Zainal Abidin, Zaima Azira (Universiti Teknologi Malaysia, 2015)
Actinomycetes are biotechnologically important for their unrivalled capacity to produce bioactive secondary metabolites. Although thousands of antibiotics have been discovered from actinomycetes, these represent only a small fraction of the entire reservoir. Thus, screening of actinomycetes from poorly studied environment is a valuable attempt. In the present study, an effort was made to isolate, identify and evaluate the antimicrobial activities of actinomycetes from Tanjung Lumpur Mangrove Forest of Pahang, Malaysia; an underexplored ecosystem. Out of 1366 actinomycetes that were successfully enumerated, a total of 40 representative isolates were selected for further evaluation. The antimicrobial activity of the representative isolates were first assessed using the cross streak method against Bacillus subtilis, Candida albicans, Escherichia coli, Serratia marcescens and Staphylococcus aureus. Twenty five isolates displayed antagonistic potential against at least one of the test organisms. Of this, 40% exhibited antibacterial activity, 24% exhibited antifungal activity and 36% displayed both. The cell–free supernatant of the active isolates were then further evaluated using the agar well diffusion method, in which only 4 isolates displayed inhibitory activity. A total of 13 representative isolates were identified and characterized using 16S rRNA gene partial sequencing. They were further classified into 7 genera namely Streptomyces, Micromonospora, Rhodococcus, Gordonia, Pseudonocardia, Mycobacterium and Actinophytocola. These findings suggested that mangrove of Tanjung Lumpur is a rich source of actinomycetes for the discovery of bioactive secondary metabolites. Keywords: Diversity, mangrove, actinomycetes, Tanjung Lumpur, antimicrobial activity